2016
DOI: 10.1186/s13550-016-0236-1
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium-90 radioembolization for colorectal cancer liver metastases: a prospective cohort study on circulating angiogenic factors and treatment response

Abstract: BackgroundYttrium-90 radioembolization (90Y-RE) as a treatment for liver tumours induces radiation damage and hypoxia in liver tissue, which is also a trigger for systemic release of angiogenic factors, potentially stimulating tumour growth. We examined changes in circulating angiogenic factors following 90Y-RE and investigated the association between response and angiogenic factors. In this prospective study, 42 patients with unresectable, chemorefractory metastatic colorectal cancer (CRCLM) were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Additionally, serum levels of circulating VEGF and PDGF for different time points were significantly different among patients who responded and did not respond to treatment. Similarly, Rosenbaum et al ( 13 ) found a significant increase in serum VEGF, HGF and Ang-2 levels after TARE in 42 CRCLM patients. Carpizo et al ( 9 ) also reported an increase >50% over the baseline in serum angiogenic factor levels in patients who received TARE for HCC and CRCLMs.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Additionally, serum levels of circulating VEGF and PDGF for different time points were significantly different among patients who responded and did not respond to treatment. Similarly, Rosenbaum et al ( 13 ) found a significant increase in serum VEGF, HGF and Ang-2 levels after TARE in 42 CRCLM patients. Carpizo et al ( 9 ) also reported an increase >50% over the baseline in serum angiogenic factor levels in patients who received TARE for HCC and CRCLMs.…”
Section: Discussionmentioning
confidence: 77%
“…However, most of them have been designed to evaluate the angiogenic response after TACE for HCC ( 16 , 17 , 18 , 19 ). In contrast, data on the angiogenic response after TARE for CRC liver metastases are limited to two studies ( 9 , 13 ). For this reason, in this pilot study, we analyzed the angiogenic response after TARE in CRCLM patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a difference in median OS with and without the presence of extrahepatic metastases at baseline, respectively 7 versus 10 months (p = 0.0018). Several other studies with a comparable patient population also found that extrahepatic disease was a predictor of survival after radioembolization [24,[45][46][47][48][49]. Other known prognostic factors are tumor load, baseline CEA level, and location (left-versus right-sidedness) of the primary tumor [24,49,50].…”
Section: Discussionmentioning
confidence: 93%
“…However, few studies on the existence of the angiogenesis response after TARE have been published. 13,14,24 Only two studies investigate the angiogenesis response after TARE in patients with HCC. Carpizo et al 13 applied TARE with Yttrium-90-loaded on resin microspheres to 22 patients with primary and secondary liver tumors (7 HCC and 15 colorectal carcinoma metastases).…”
Section: Discussionmentioning
confidence: 99%